L2 and L3 Intrusions on L1 Production: Language Choice and Code-Switching in Indonesian Trilingual - Engliana Engliana (Journal of English Language and Culture, 2020)
There has been multitude studies on bilingualism, yet this paper explores the trilingualism in Indonesian context. Although this case study cannot represent the whole population speaking three language in Indonesian context, it is true that the intrusions may occur due to language choice and the environmental factors as Grosjean proposes that the code switching behavior is a result of language choice in a particular setting, interactions, topics included, and the interaction functions. Using questionnaire to gather language background, language use, and language choices together with recording tape to record the conversation with the participant, the findings support Grosjean’s model of language activation of trilingualism and there are some environmental factors caused trilingual chooses the language she speaks.